EVALUASI KELAYAKAN USAHA TERNAK AYAM PEDAGING DI KABUPATEN SLEMAN - Kadarso Kadarso; Retno Lantarsih (Jurnal Dinamika Sosial Ekonomi, 2007)
The aim of this research are to low : (1) financial feasibility; (2) sensitivity of broiler livestok; (3) duration return of capital ; and (4) break even point .The basic method of this research is descriptive analysis by using cross section data of broiler livestock in the year 2006/2007 that is at Avian Influenza epidemic in Indonesia. Intake of breeder sample use random sampling method. The result of reseanch indicate that at the time of happened a influenza epidemic in Indonesia at year 2006/2007: (1) the broiler livestock is feasible,(2)  the broiler livestock is sensitive to change of cost production; (3) Duration of capital is 9 months 29 day, (4) break even point at earnings 45.850.42SKeywords:Financial Feasibility, Sensitivity, BEP, Broiler